2020
DOI: 10.5090/kjtcs.2020.53.2.41
|View full text |Cite
|
Sign up to set email alerts
|

Chylothorax after Surgery for Congenital Cardiac Disease: A Prevention and Management Protocol

Abstract: This article was presented at the 50th Annual Meeting of the Korean Society for Thoracic and Cardiovascular Surgery. Background: Chylothorax after congenital heart surgery is not an uncommon complication, and it is associated with significant morbidity. However, consensus treatment guidelines are lacking. To improve the treatment outcomes of patients with postoperative chylothorax, we implemented a standardized management protocol at Severance Hospital in September 2014. Methods: A retrospective review of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 14 publications
2
25
1
Order By: Relevance
“…21 Shin et al have reported their incidence of 5% after BCPS surgery. 20 We had a fairly low incidence of chylothorax (2%) in our series, of which more than half required thoracic duct ligation.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…21 Shin et al have reported their incidence of 5% after BCPS surgery. 20 We had a fairly low incidence of chylothorax (2%) in our series, of which more than half required thoracic duct ligation.…”
Section: Resultsmentioning
confidence: 64%
“…Chylothorax after congenital heart surgery has been reported ranging from 2 to 5%. 20,21 Although the incidence per se of this complication is low, it can lead to serious complications such as malnutrition, infection, and immunosuppression causing greater morbidity and mortality following pediatric cardiac surgery. 21 Shin et al have reported their incidence of 5% after BCPS surgery.…”
Section: Resultsmentioning
confidence: 99%
“…While low-fat diets have become a part of chylothorax management for many, there is no data to demonstrate low-fat diets or nothing per os are bene cial. Studies, particularly in those with congenital heart disease, have not been done randomizing patients with chylothorax to a low-fat diet or normal fat diet and comparing the two groups [10,17,18]. Data for low-fat diets comes from case reports and retrospective reviews which cannot differentiate the effect of time versus the effect of the low-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical management protocols have been described. While many of these have been associated with a decrease in chest tube duration and hospital length of stay, speci c components of the protocol mediating these improvements have not been delineated [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“… 1 3 The characteristics of postoperative chylous effusion fluid include lymphocytic predominance and high triglyceride count. 4 , 5 Secondary chylothoraces result in significant morbidities, including prolonged ventilator dependence, intensive care stays, malnutrition, prolonged parenteral nutritional support, hypoalbuminemia, lymphopenia, immunodeficiency, electrolyte abnormalities, nosocomial infections, and death. 6 8 Despite severe morbidities and mortality, little is known about the causes of postoperative chylothorax.…”
Section: Introductionmentioning
confidence: 99%